Politics and reconciliation : a critical juncture for state building (2017)
We describe some features of the political environment in Colombia, drawing from a unique panel dataset of about 10,000 households. Contrasting responses in 2013 and 2016, we document a persistent lack of interest in politics and prevailing clientelism, with personalistic links dominating partisan affinity. Engagement in clientelistic vote buying, instead, is quite variable in time, with households getting into and out of these exchanges. Rejecting the simplest and more optimistic theories of modernization, we do not find that increases in household wealth correlate with the abandonment of clientelism. Instead, changes in the weakness of the state (as proxied with tax evasion) correlate strongly with changes in clientelism. Strengthening the state therefore seems a priority. Viewing peace-building efforts as one key step in this direction naturally leads to the examination of the attitudes towards the recent peace process between the government and the Farc, Colombia's largest guerrilla group. With a special set of questions included in 2016, we also study households' perspectives on this topic. The data reveals a rare combination of indifference and polarization towards the peace process...